Incidencia de mastitis en vacunos de leche en el establo “LÁCTEA”- Virú - Negreiros Narro, José Alejandro (2019)
The present study was based on the incidence of mastitis in Holstein cattle, was carried out with the purpose of determining the incidence of mastitis, also, to identify the mastitis index during the 2016-2017 period and to calculate the economic losses due to incidence of mastitis in the study period. The study was conducted in the stable "LACTEA", located in La Antena, km 531 Virú province, Virú district in the department of La Libertad. The statistical method used was the descriptive one. The methodology was based on calculating the percentage of clinical mastitis, both the incidence and the rate of it within the years 2016 - 2017. The results obtained are: the incidence of mastitis of 2016 in the 1st. Breastfeeding:18.2%; 2nd lactation: 27.3%; 3rd lactation: 8.7%; 4th lactation: 0% and 2017 in the 1st lactation: 13.6%; 2nd lactation: 9.1%; 3rd lactation: 4.3%; 4th lactation: 4.3%; the incidence rate of mastitis was 13% in 2016 and 8% in 2017. The microorganisms that occurred most frequently were: Staphylococcus aureus in 33%, Escherichia coli in 67%. Finally, the economic loss per cow is $ 124, average. It is concluded that both the incidence and rate of mastitis are below the established